2012
DOI: 10.1002/chem.201201042
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Cycloaddition of Carbon Dioxide and Epoxides Catalyzed by Cobalt‐Substituted 12‐Tungstenphosphate

Abstract: Co(II)-substituted α-Keggin-type 12-tungstenphosphate [(n-C(4)H(9))(4)N](4)H[PW(11)Co(H(2)O)O(39)]-(PW(11)Co) is synthesized and used as a single-component, solvent-free catalyst in the cycloaddition reaction of CO(2) and epoxides to form cyclic carbonates. The mechanism of the cycloaddition reaction is investigated using DFT calculations, which provides the first computational study of the catalytic cycle of polyoxometalate-catalyzed CO(2) coupling reactions. The reaction occurs through a single-electron tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 47 publications
2
27
0
Order By: Relevance
“…At 224 K the clear appearance of an additional set of peaks was observed indicating the presence of an additional compound. DFT calculations carried out in the past on Ru III ‐ and Co II ‐substituted Keggin anions, [Ru III SiW 11 O 39 ] 5– and [Co II PW 11 O 39 ] 5– , showed two plausible coordination modes, a higher energy “end‐on” coordination and a lower energy more stable “side‐on” coordination, Scheme , . The 31 P NMR spectra support the idea of “side‐on” coordination” at room temperature down to ca.…”
Section: Resultsmentioning
confidence: 71%
“…At 224 K the clear appearance of an additional set of peaks was observed indicating the presence of an additional compound. DFT calculations carried out in the past on Ru III ‐ and Co II ‐substituted Keggin anions, [Ru III SiW 11 O 39 ] 5– and [Co II PW 11 O 39 ] 5– , showed two plausible coordination modes, a higher energy “end‐on” coordination and a lower energy more stable “side‐on” coordination, Scheme , . The 31 P NMR spectra support the idea of “side‐on” coordination” at room temperature down to ca.…”
Section: Resultsmentioning
confidence: 71%
“…[1][2][3], four reactions were carried out at four different concentrations (n) of BIT-C, respectively. Catalyst and co-catalyst were completely dissolved in 1,2-epoxyoctane before reacting.…”
Section: Mechanistic Investigations: Kinetic Analysis Of Bit-c and Bumentioning
confidence: 99%
“…Meanwhile, a large number of homogeneous and heterogeneous catalysts have been reported, such as metal-salen complexes [5], ionic liquids [6], nitrogen-containing polymers [7], metal oxides [8], organocatalysts [9], and metal-organic frameworks (MOFs) [10,11]. In our previous work, the transition metal-substituted polyoxometalates (POMs) were also found to be effective catalysts for CO 2 cycloaddition to epoxides as the single-component catalysts [1,12,13]. Unfortunately, relatively high temperature (>100°C) and high CO 2 pressure (>2.0 MPa) are generally required in most of catalytic systems, which greatly limit practical application.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…For systems containing redox active metals such as Co in α-Keggin-type structures calculations have also shown that ring opening of the epoxide can occur without the intervention of a nucleophilic agent through electron transfer and oxidation of the metal cente. 24 To realise cyclic carbonate production on a large scale, epoxides themselves will have to be synthesised by the oxidation of alkenes. The direct synthesis of cyclic carbonates from olefins, avoiding additional work-up procedures, would be an interesting and economically feasible route.…”
Section: Introductionmentioning
confidence: 99%